2013
DOI: 10.1074/jbc.m112.441295
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-permeable C-terminal Dopamine Transporter Peptides Attenuate Amphetamine-evoked Dopamine Release*

Abstract: Background:The significance of dopamine transporter (DAT) C-terminal protein-protein interactions for amphetamineinduced dopamine efflux is unsettled. Results: Cell-permeable C-terminal DAT peptides attenuate amphetamine-induced dopamine efflux and locomotor activity in mice. Conclusion: DAT C-terminal protein-protein interactions are critical for the effects of amphetamine in vivo. Significance: Targeting protein-protein interactions might be a way of inhibiting the effects of psychostimulants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 50 publications
(44 reference statements)
1
22
0
Order By: Relevance
“…Cocaine CPP was also sensitive to manipulations of the NET-Thr 30 motif by the TAT-NET-Thr 30 peptide strategy. TAT-conjugated DAT carboxyl-terminal peptide, which disrupts DAT-Ca 2ϩ /calmodulin-dependent protein kinase II␣ interaction, attenuates amphetamine-stimulated locomotor activity in mice when administered systemically (38). These studies indicate that TAT peptides effectively reach brain regions following systemic administration and elicit their effects on psychostimulant-mediated behaviors.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Cocaine CPP was also sensitive to manipulations of the NET-Thr 30 motif by the TAT-NET-Thr 30 peptide strategy. TAT-conjugated DAT carboxyl-terminal peptide, which disrupts DAT-Ca 2ϩ /calmodulin-dependent protein kinase II␣ interaction, attenuates amphetamine-stimulated locomotor activity in mice when administered systemically (38). These studies indicate that TAT peptides effectively reach brain regions following systemic administration and elicit their effects on psychostimulant-mediated behaviors.…”
Section: Discussionmentioning
confidence: 73%
“…Thus, we had six groups of mice: saline/vehicle (n ϭ 9), saline/TAT-NET-Thr 30 (n ϭ 9), saline/TAT-NET-T30A (n ϭ 9), cocaine/ vehicle (n ϭ 9), cocaine/TAT-NET-Thr 30 (n ϭ 9), and cocaine/ TAT-NET-T30A (n ϭ 9). The concentration of TAT-NET peptides was fixed at 12 mg/kg (300 g per mouse of ϳ25-g body weight) based on previous studies (37,38) and following our initial testing with varying concentrations of TAT-NETThr 30 peptide. Preference scores measured in seconds reflect the time the mice spent in the drug-paired side during postconditioning day subtracted from the time spent in the drug-paired side preconditioning when baseline scores were taken.…”
Section: Conditioned Place Preferencementioning
confidence: 99%
“…Finally, a mutant DAT with Ala substitutions of residues 612-614 failed to support enhanced AMPH-induced DA efflux by CaMKIIa overexpression. Subsequent studies by the Gether laboratory demonstrated the ability of the DAT C24 peptide to block DAT-CaMKIIa interactions in vivo as well as AMPH-evoked DA efflux and AMPH-induced locomotor hyperactivity (Rickhag et al, 2013). Together, these studies make a compelling case that CaMKIIa both associates with DAT and regulated the functional states of the transporter, as manipulated by AMPH.…”
Section: A Regulation Of Dopamine Transporter Bymentioning
confidence: 90%
“…Recently, two different dopamine transporter knock-in mice with disrupted PDZ-binding motifs (DAT-AAA and DAT+Ala) were created (Rickhag et al, 2013). These mutants are characterized by dramatic loss of dopamine transporter expression in the striatum, spontaneous hyperlocomotion and attenuated response to amphetamine thereby validating a critical role of PDZ-domain interactions for synaptic distribution of DAT (Rickhag et al, 2013).…”
Section: Other Dat Mutant Micementioning
confidence: 99%